The Transformation of the Russian Federation Foreign Policy Doctrine and its South Caucasus Component until 2022 - Gevondyan, Alen (YSU Journal of International Affairs, 2022)
Since the collapse of the Soviet Union and restoration of the independence Russian Federation has developed 5 foreign policy doctrines (1993, 2000, 2008, 2013, 2016). Right after the restoration of the independence the main purpose of the foreign policy doctrines was to adapt to the new realities and fix Russia’s role in it. Later, it was changed. The main goal became the realization of multipolar policies, including cooperation with China, India, and other countries.It is worth mentioning that in all Doctrines special importance has been attributed to the post-soviet region, including the South Caucasus. On the one hand Moscow was actively cooperating with the South Caucasian States, from the other hand it was trying to engage in existing conflict resolution formats as a mediator. Simultaneously Russia was pushing South Caucasian States to engage in the ongoing integration initiatives
Keywords: RF; foreign policy doctrine; South Caucasus; CSTO; EAEU; integration; Nagorno Karabakh; the Republic of Armenia; Azerbaijan